2000
DOI: 10.2337/diabetes.49.12.2116
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal compensation for fat-induced insulin resistance includes reduced insulin clearance and enhanced beta-cell response.

Abstract: Central adiposity is highly correlated with insulin resistance, which is an important risk factor for type 2 diabetes and other chronic diseases. However, in normal individuals, central adiposity can be tolerated for many years without development of impaired glucose tolerance or diabetes. Here we examine longitudinally the mechanisms by which glucose tolerance can be maintained in the face of substantial insulin resistance. Normal dogs were fed a diet enriched with moderate amounts of fat (2 g · kg -1 · day -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
158
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 44 publications
17
158
6
Order By: Relevance
“…Nevertheless, a fat feeding experiment in animals showed an inverse relationship between hepatic insulin uptake and pancreatic insulin secretion, a finding which is consistent with our observation that percent hepatic insulin extraction increases with deteriorating glucose homeostasis [41]. Increased hepatic uptake of newly secreted insulin could help counteract the impaired suppression of hepatic gluconeogenesis accompanying a deficit in first-phase pancreatic insulin output.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, a fat feeding experiment in animals showed an inverse relationship between hepatic insulin uptake and pancreatic insulin secretion, a finding which is consistent with our observation that percent hepatic insulin extraction increases with deteriorating glucose homeostasis [41]. Increased hepatic uptake of newly secreted insulin could help counteract the impaired suppression of hepatic gluconeogenesis accompanying a deficit in first-phase pancreatic insulin output.…”
Section: Discussionsupporting
confidence: 90%
“…Reduced insulin clearance has important implications in the pathophysiology of T2DM and IGR. For example, animal models have shown that decreased insulin clearance serves as a compensatory mechanism to preserve b-cell function and maintain peripheral insulin levels in the states of insulin resistance (29). It is tempting to hypothesize that sclerostin might have a role in modulating insulin clearance by acting on the Wnt signaling pathway in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between dietary fat/carbohydrate ratio and insulin clearance would lead us to postulate that racial differences in dietary intake might be responsible. In animal experiments, after only one week of a diet enriched with a moderate amount of fat, there is a decline in insulin clearance (31). This has been proposed to be a compensation for fat-induced insulin resistance preceding the increase in insulin secretion (31).…”
Section: Discussionmentioning
confidence: 99%